Transmission support using Wind Farm controls during voltage stability emergencies. (February 2017) - Vournas, Costas; Anagnostopoulos, Ioannis; Souxes, Theodoros
Abstract: This paper investigates the effect of reactive support by Wind Farms (WF) on the maximum power transfer, and thus the voltage stability limit of a transmission system. An insecure snapshot in a weak area of the Hellenic Interconnected System is examined, as well as a simpler test system. MV feeder characteristics and substation controls (feeder resistance and reactance, switched capacitors, LTC controls) are modelled in detail. Most importantly, the converter current limits, as well as the overvoltage limitations on the MV feeder, are taken into consideration in assessing the effect of the WF support. Graphical abstract: Highlights: The effect of WF reactive power support under emergency conditions is presented. A considerable increase in maximum power transfer (MPT) using WF controls is achieved. MV feeder characteristics and substation controls are modelled in detail. With a continuous HV control scheme the MPT of a weak corridor is greatly increased. A single command intelligent control is proposed giving the same MPT results.